Internet of Things-based telemonitoring rehabilitation system for knee injuries - Muheeb Musaed M. Al-Omri; Nayef Abdulwahab Mohammed Alduais; Mohamad Nazib Adon; Abdul-Malik H. Y. Saad; Antar Shaddad H. Abdul-Qawy; Tole Sutikno (Bulletin of Electrical Engineering and Informatics, 2020)
Rehabilitation engineering, as one of the active research areas in biomedical science, needs further investigations and improvements. The process of rehabilitation, whether after a stroke, ligament, or accident-related injuries, is commonly based on clinical assessment tools, which can be executed, either by self-reported (home-based) treatment or through observer-rated therapy. However, people with reduced mobility (e.g., stroke, surgical, and ligament patients) can benefit from rehabilitation programs only if effective and appropriate assistive tools are provided. In this paper, a new Internet of Things (IoT)-based telemonitoring system is introduced for knee injuries’ rehabilitation (Knee-Rehab). The proposed system is a real-time rehabilitation and monitoring framework designed to be a portable, home-based, and online-based instrument comprised of bio-mechanical, bio-instrumentation and IoT-based elements. The system helps patients to rest at home after surgeries or physical treatment, do their rehab-exercises, and receive suggestions form their advisors, which gain the ability to monitor the situation over the exercising time and propose necessary medication/activities to be followed by the patients accordingly, based on their current status. The experimental measurements show the high accuracy achieved by the developed system in terms of monitored knee joint angle, where the maximum error is 3.5° compared to manual goniometer measurements.